Enabling real-time robot-tracker communication via MQTT on the factory cloud for metrology automation - Asif, Seemal; Hall, Jon; Sawyer, Daniela (Institute of Electrical and Electronics Engineers (IEEE), 2025)
In large-scale precision manufacturing, achieving real-time high-precision alignment between industrial robots and metrology systems remains challenging. This paper proposes a cloud-integrated communication architecture that enables real-time, bidirectional data exchange between industrial robots and laser trackers. The system leverages the MQTT publish/subscribe protocol within the AMRC Factory+ cloud environment to orchestrate metrology data flows. Robot controllers publish motion commands while laser trackers provide real-time position feedback, forming a closed-loop calibration process. Measurement data is processed through dedicated adapter layers and calibration modules, then disseminated by an MQTT broker to a central control system which computes alignment corrections and updates robot motion. The architecture employs edge computing and cloud services for modularity, scalability, and low latency, and integrates with existing metrology software (e.g., Spatial Analyzer, PolyWorks). These findings underscore the efficacy of cloud-based robot-tracker coordination for dynamic, highprecision calibration and control. The proposed approach provides a robust foundation for future Industrial IoT (IIoT) deployments in metrology-driven manufacturing systems.
Keywords: 46 Information and Computing Sciences; 4014 Manufacturing Engineering; 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; Networking and Information Technology R&D (NITRD); 9 Industry, Innovation and Infrastructure; MQTT communication; cloud-based metrology; industrial IoT; real-time robot calibration; High Precision Manufacturing